Motivasi Siswa Dalam Mengerjakan Tugas Mata Pelajaran Sejarah Kebudayaan Islamdi MTsN6 Agam - Putri, Bunga Pratama; Junaidi , Junaidi; Iswantir M, Iswantir M; Arifmiboy, Arifmiboy (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated by the problem where students are oftenlate to work and collect assignments and even do not do assignments at all. Plus the learning method used in the lesson is the lecture method which causes students to feel bored and sleepy quickly and causes learning to be passive. The type of research used is field research with the method applied is descriptive qualitative method. Data collection techniques by means of interviews and observations. This research was conducted at MTsN 6 Agam, which consisted of two informants, namely key informants and supporting informants to obtain valid data. Key informants are students and supporting informants are teachers in the field of Islamic cultural history studies. Then the author performs data analysis with analytical analysis. The author uses data triangulationas a technique to check the validity of the data. Based on the results of the research that the author has done, it can be concluded that students are lazy to do the tasks that have been given because they have bad habits in learning.Likes to procrastinate doing assignments, copying friends' assignments and not doing assignments.The inability of students to do assignments is due to the difficulty of students in understanding the history of Islamic culture. Students often feel bored and sleepy when studying the history of Islamic culture. They assume that the history of Islamic culture is a difficult subject, making students neglectful in learning and not being too enthusiastic about learning.